Factors influenceing long-term prognosis in male patients surviving a first coronary attack. Issue 2 (February 1975) - Mulcahy, R; Hickey, N; Graham, I; McKenzie, G
Abstract : Three hundred and sixty-four men who survived a first episode of acute coronary insufficiency or myocardial infarction for 28 days were admitted to a coronary heart disease secondary programme between 1 January 1961 and 31 December 1971. Of these, 252 have been followed for at least 4 years. The 4-year mortality was 13.5 per cent (34 patients). The average mortality was 3.4 per cent but an excess of deaths occurred during the first year of follow-up. Of 11 characteristics measured during the acute attack, only severity of the attack was significantly associated with poor 4-year survival. Cigarette consumption after infarction was significantly less among those surviving the 4-year period when compared with decedents. Follow-up systolic and diastolic blood pressure levels were significantly lower among decedents. No significant differences were noted in serum cholesterol levels and in mean weight, The presence of post-infarction angina did not affect the prognosis.